Estonian Traffic Behaviour Monitoring Studies 2001–2016: Overview and Results - Ess, Juri; Antov, Dago (The Baltic Journal of Road and Bridge Engineering, 2017)
One of the most significant factors affecting road safety is human. Estonia has improved road safety dramatically since its re-independence in 1991, and among the other reasons, this has happened due to changes in behaviour of road users. Likely, at the same time, there have been annual studies conducted, aimed at measuring specific indicators connected to compliance with road traffic law. As a result, one gets long-term trends in such indicators as compliance with traffic signals, usage of seat belts, yielding to pedestrians at uncontrolled crossings. This paper aims to describe Estonian traffic behaviour studies, analysing their results and pointing out actual problems in traffic behaviour. According to the results of studies, all aspects of traffic behaviour showed positive trends, but these trends are different. Certain indicators such as usage of seat belts have changed dramatically, while others like compliance with traffic signals showed only moderate changes. The foremost problem in traffic behaviour is found out to be ignorance to yield at uncontrolled pedestrian crossings. It is certainly one of the issues to deal with in the context of achieving Estonian strategic goals in road safety.